First direct evidence of reproductive behaviour of the white grouper, Epinephelus aeneus (Geoffroy Saint-Hilaire, 1817) - DESIDERÀ, ELENA; MAGNANI, LUANA; NAVONE, AUGUSTO; GUIDETTI, PAOLO; MAZZOLDI, CARLOTTA (Mediterranean Marine Science, 2019)
This study describes the first ever reported direct observation of a pair spawning event and the reproductive liveries of the white grouper, Epinephelus aeneus. Spawning took place on a rocky bank located in the Marine Protected Area (MPA) of Tavolara-Punta Coda Cavallo (NE Sardinia, Italy), in the Western Mediterranean Sea. In the evening of August 4th, 2018, the spawning of two large-sized individuals ( 90 cm total length), displaying distinct colour patterns, was observed using SCUBA diving. This direct observation is the first record of E. aeneus male reproductive livery, characterized by a darker coloration on the head, the dorsal part of the body and the caudal fin. In addition, information on the environmental conditions in which reproduction occurred was collected. At the study site, relatively high seawater temperatures were recorded at the time of the E. aeneus spawning (24 °C at 24.7 m), as well as over the 2018 summer months (July-September), even in deep waters (>35 m), compared to previous summers. The spawning event occurred in a coralligenous-dominated seascape where fishing is prohibited, while diving activities are allowed. The site hosts abundant populations of ecologically and commercially valuable fish species (e.g., groupers, sparid fishes), with significant proportions of large-sized individuals (i.e. reproducers). Further studies are needed to advance our knowledge of the white grouper, with a particular emphasis on reproduction and the importance of implementing effective protection measures. Prioritizing management actions at key reproductive sites, such as rocky banks, is essential for ensuring the protection and/or recovery of over-exploited species.